Le régime juridique des langues dans l'administration publique au Nouveau-Brunswick - Foucher, Pierre; Snow, Gérard (Les Cahiers de droit, 1983)
Linguistic rights in New Brunswick have progressed since the enactment of the Official Languages of New Brunswick Act of 1969. The Canadian Charter of Rights and Freedoms has caused the entrenchment of some linguistic guarantees in the Constitution and has provided for judicial enforcement. Collective rights have also been given legislative sanction through the passing, in 1981, of An Act Recognizing the Equality of the Two Official Linguistic Communities in New Brunswick, and new legislation to replace the 1969 Act has now been proposed in a recent government-sponsored study. This paper looks at the legal consequences of these enactments in relation to public administration in New Brunswick.